On Determinants Of The Economic Growth Of European Countries During 2005–2015 - Mazurek, Jiří (Comparative Economic Research. Central and Eastern Europe, 2017)
The aim of the paper is to examine the economic growth of 32 European countries from 2005 to 2015. This period was characterized by a strong growth prior to 2009, when the Great Recession started, and lasted until 2012–2013 in the majority of examined countries. The growth between 2005 and 2015 was studied with regard to six selected socio-economic factors: initial level of the gross domestic product, economic openness, democracy index, human capital, physical capital, and foreign direct investments. The main result is that the growth was directly proportional to human and physical capital, and indirectly proportional to the initial level of GDP and the democracy index. Furthermore, cluster analysis showed that the historical division of Europe into “West” and “East” still persists to a considerable extent.